Correlation analysis between Reddit sentiments and Ether (ETH) price action - Leah, Castillo (Nanyang Technological University, 2022)
Cryptocurrencies (Crypto) have seen a tremendous growth in recent years. According to CNBC, the adoption of Cryptocurrencies around the world was up by 881% in the year 2020 [1] Several factors contributed to Crypto’s rise, among them is due to a rising number of businesses across a variety of industries embracing cryptocurrencies. These businesses allow their customers to pay with crypto in exchange for their goods and services, officially acknowledging cryptocurrencies as an alternative form of payment [2] Furthermore, Cryptocurrencies are now being recognized as an alternative form of investment, with Morgan Stanley leading the way in offering their clients access to Bitcoin funds [3] As a result, interest in the study of cryptocurrencies and its’ market behaviour are ever growing.